Retailing in an Age of Change: Lessons from the Dynamic Saudi Arabian Market - Farzad Kazemi (Journal of World Economy, 2025)
This study examines the key factors for the survival and success of new retail stores in Saudi Arabia. Due to economic growth and population growth, the retail sector in this country has witnessed the emergence of numerous stores, many of which have faced serious challenges and have been eliminated from the competition. Using a qualitative method and interviews with 17 retail industry experts, this study identified the essential elements at the time of establishment and effective strategies for the survival of new businesses. The findings show that determining the organizational vision and mission, market analysis, choosing a strategic location, managing expert human resources and using modern technologies are among the key factors for success. Also, the use of Kaizen theory, careful financial monitoring and crisis management through the formation of working groups play an important role in the survival of these businesses. By providing practical models and applicable strategies, this study helps investors and managers of new stores to make more informed decisions and prevent potential failures. The results of this study can be used as a guide for the sustainable development of retail businesses in competitive environments and help improve the conditions of small businesses and economic development.